MODEL-MODEL PENGEMBANGAN KAJIAN PSIKOLOGI DALAM DISKURSUS PEMIKIRAN MUSLIM KONTEMPORER - Abidin, M Zainal (Religi: Jurnal Studi Agama-agama, 2012)
This paper discusses the models of developing the psycholog y stud- ies in Islamic muslim contemporary discourse. Here, mentioned that there are two ways in developing psychology studies in Islamic world. Firstly, based on the tradition of Islam itself, named turats, and sec- ondly, started from modernity (hadÃ¢tsah). Psychology studies that based on the turats usually called Islamic psycholog y developed from the Islamic knowledge such as Islamic philosophy and Sufism. While, psy- chology studies that started from modernity, called as the psychology of Islam, developed from the western psychology that fitted with the Islamic value. Between both of them, psychological studies that come from Islamic tradition have extra value. Here, to study psycholog y from the tradition of Islamic philosophy is a good way in developing psychology studies more comprehensive. Actually, the intensive dia- logue between the tradition of Islam and modern psychology studies will very helpful in finding the essence of Islamic psychology.